Preparation method and application of CoS / Ti3C2TxMXene inversion heterojunction self-healing conductive hydrogel electrode material

By combining CoS/Ti3C2TxMXene inverse heterojunction with PAA/CS hydrogel, a physical dual network structure is constructed, which solves the problems of low specific capacitance and insufficient mechanical strength of conductive hydrogel, and realizes a conductive hydrogel electrode material with high specific capacitance, good mechanical properties and self-healing function.

CN119724957APending Publication Date: 2025-03-28HUBEI UNIV OF AUTOMOTIVE TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411910367.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing conductive hydrogels have low specific capacitance and insufficient mechanical strength, making them difficult to meet the needs of flexible electronic equipment, and are easily affected by external factors during use, resulting in damage, reducing the life of the material.

Method used

CoS/Ti3C2TxMXene inverse heterojunction junction is combined with PAA/CS hydrogel matrix, and CoS/Ti3C2TxMXene inverse heterojunction powder is synthesized in situ by hydrothermal method to construct a physical dual network structure to realize the self-healing characteristics of conductive hydrogels.

Benefits of technology

It improves the specific capacitance and mechanical strength of the conductive hydrogel, realizes the self-healing function, extends the life of the material, and improves the electrochemical activity and ion diffusion ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724957A_ABST
    Figure CN119724957A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a CoS / Ti < 3 > C < 2 > T < x > MXene inversion heterojunction self-healing conductive hydrogel electrode material, CoS nano particles grow on the surface of Ti < 3 > C < 2 > T < x > MXene through an in-situ hydrothermal method to form an inversion heterojunction, and then a PAA / CS / CoS / Ti < 3 > C < 2 > T < x > MXene (PCCT) conductive hydrogel electrode material of a double physical cross-linked network is synthesized through a two-step method. The three-dimensional porous structure of the PCCT conductive hydrogel electrode material can provide an appropriate geometric space and an appropriate electronic structure, active substance accumulation under high-quality load can be inhibited, and the specific capacitance of the PCCT conductive hydrogel electrode material is improved; when the current density is 4mA / g, the specific capacitance is 3.6 F / g; when the current density is 10mA / g, the cycling stability is still as high as 80% after 2000 times of cycling; after the PCCT conductive hydrogel is healed at room temperature for 48 hours, the self-healing efficiency of the PCCT conductive hydrogel can reach 66.88%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy materials and devices, in particular to a CoS / Ti3C2T x Preparation method and application of MXene inverse heterojunction self-healing conductive hydrogel electrode material. Background Art

[0002] The booming development of flexible wearable electronic products has put forward higher requirements for the miniaturization and flexibility of energy storage devices. Flexible solid-state supercapacitors (FSSCs), as a new generation of wearable energy storage devices, have the advantages of fast charge and discharge rate, high power density, long cycle life and safety, and have attracted widespread attention. However, the low energy density of FSSCs limits its commercial application value, so the development and design of electrode materials with high specific capacitance is one of the important ways to solve key problems.

[0003] Compared with traditional hydrogels, conductive hydrogels have multiple functions, such as lightness, portability, biocompatibility, self-healing and superior mechanical stability. The research on conductive hydrogels mainly focuses on carbon materials such as activated carbon (AC), CNTs, graphene and rGO or pseudocapacitive electrode materials. Pseudocapacitive electrode materials are generally binary or ternary metal oxides / hydroxides and conductive polymers (PANI, PPy, poly 3,4-ethylenedioxythiophene (PEDOT)). 3D network hydrogel is a conductive hydrogel with large specific surface area, porous structure and fast mass transfer and power transfer kinetics. It has received extensive attention in the research of flexible electrode materials for supercapacitors. However, the low conductivity and poor mechanical strength of conductive hydrogels limit their practical application in flexible electronic devices. In addition, during use, they are affected by some external factors, which will cause a certain degree of damage to this type of material. This damage will affect the normal use of the material and reduce the life of the material. As a result, the specific capacitance and cycle life of conductive hydrogels still cannot meet the requirements of portable wearable electronic products. Summary of the invention

[0004] Technical problem to be solved: In view of the technical problems existing in the background technology, the present invention provides a CoS / Ti3C2T x The preparation method and application of MXene inverse heterojunction self-healing conductive hydrogel electrode material solve the problem of low specific capacitance of existing conductive hydrogels and develop electrode materials that can achieve self-healing, so that flexible all-solid-state supercapacitors can obtain good energy storage characteristics and long-term durability.

[0005] Technical solution: A CoS / Ti3C2T xA method for preparing a MXene inverse heterojunction self-healing conductive hydrogel electrode material, the preparation method comprising the following steps: Step 1: Prepare CoS / Ti3C2T x MXene inverse heterojunction powder; Step 2: Dissolve a certain amount of chitosan CS in glacial acetic acid solution and mix the CoS / Ti3C2T x MXene inverse heterojunction powder and aqueous solutions of acrylic acid, initiator and crosslinker were added to the above mixed solution and placed in a blast drying oven for full reaction; the reactants were immersed in a saturated sodium chloride solution to obtain a PAA / CS / CoS / Ti3C2T dual physical crosslinked network structure. x MXene conductive hydrogel electrode materials.

[0006] Preferably, in step 1, CoS / Ti3C2T x Specific preparation steps of MXene inverse heterojunction powder: Step S1: Add 7 mmol CoCl2·6H2O and 28 mmol thiourea into 60 ml ethylene glycol solution, the volume ratio of the ethylene glycol solution is V 水 :V 乙二醇 =4:1, stir and mix thoroughly for 20 minutes; Step S2: Add 0.1-0.5wt% of "accordion-shaped" Ti3C2T x Mxene nanosheets were treated at an ultrasonic power of 500 W for 20 min; Step S3: The mixed solution obtained in step S2 was transferred to a high-pressure reactor with a volume of 100 mL, placed in an electric heating blast drying oven, and kept warm at a temperature of 180° C. for 16 h; Step S4: After the autoclave is cooled to room temperature, the mixed solution is washed with deionized water and anhydrous ethanol and centrifuged to precipitate. The precipitate is placed in a vacuum drying oven and dried at 50°C for 18 hours to obtain CoS / Ti3C2T x MXene inverse heterojunction powder.

[0007] Preferably, the "accordion-shaped" Ti3C2T x Specific preparation steps of Mxene nanosheets: Step S 21: Under ice bath conditions, weigh 2.25g Ti3AlC2 powder and slowly add it into 15ml 40% HF solution, stir and mix, and etch it in a 37℃ water bath for 8h. After etching, wash it with deionized water by centrifugation at a centrifugal speed of 5000 rpm until the pH value of the supernatant is greater than or equal to 6; Step S 22 :Step S 21 The obtained black precipitate was dissolved in 100 ml of deionized water, and ultrasonically treated for 1 h at an ultrasonic power of 500 W in an ice bath with Ar gas continuously flowing, and then centrifuged at a centrifugal speed of 3500 rpm for 1 h. Step S 23 :Step S 22 The black precipitate obtained by centrifugation was dried in a vacuum oven at 60 °C for 12 h to obtain an accordion-shaped Ti3C2T x MXene nanosheets.

[0008] Preferably, in step 2, the amount of chitosan used is 0.24 g, the volume of the glacial acetic acid solution is 6 ml, and the solubility is 2 wt%.

[0009] Preferably, in step 2, the initiator is 0.05 g of ammonium persulfate, and the cross-linking agent is 0.081 g of FeCl3•6H2O. Ammonium persulfate and FeCl3•6H2O are dissolved in 6 ml of deionized water to prepare an aqueous solution.

[0010] Preferably, in step 2, CoS / Ti3C2T x The addition amount of MXene inverse heterojunction powder is 0.31wt%.

[0011] Preferably, in step 2, the reaction temperature of the blast drying oven is 50° C. and the reaction time is 5 h.

[0012] Preferably, the soaking time in the saturated sodium chloride solution in step 2 is 1.5 h.

[0013] The present invention also discloses a CoS / Ti3C2T x MXene inverse heterojunction self-healing conductive hydrogel electrode material, CoS / Ti3C2T x The MXene inverse heterojunction conductive hydrogel electrode material is prepared by the above preparation method.

[0014] The present invention also discloses a CoS / Ti3C2T x Application of MXene inverse heterojunction self-healing conductive hydrogel electrode materials in the preparation of positive and negative electrodes of flexible all-solid-state supercapacitors.

[0015] Compared with the prior art, the present invention has at least the following beneficial effects: 1. The present invention adopts a two-step method to quickly and efficiently synthesize PAA / CS / CoS / Ti3C2T with room temperature self-healing properties x MXene (PCCT) conductive hydrogel electrode material, CoS / Ti3C2T with high conductivity x MXene inverse heterojunction combined with PAA / CS hydrogel matrix, CoS effectively suppresses the active material Ti3C2T under high mass loading x The accumulation of MXene and the physical double network structure give the conductive hydrogel self-healing properties. CoS / Ti3C2T3 synthesized in situ by hydrothermal method x MXene inverse heterojunction powder materials, CoS and Ti3C2T x MXene can generate abundant interfaces and form abundant active centers, thus obtaining high charge transfer rate and having good electrochemical activity. x MXene helps to improve the wettability of the electrode, thereby shortening the length of the electrode / electrolyte migration path and accelerating ion diffusion. CoS nanoparticles can effectively inhibit the x The restacking of MXene improves its stability. Compared with hydrogels with only a single conductive active substance, CoS / Ti3C2T x The presence of CoS as an electron bridge in the MXene inversion heterojunction accelerates the transfer of photogenerated electrons, thus making the CoS / Ti3C2T x MXene has better electrochemical properties.

[0016] 2. The conductive hydrogel electrode material prepared by the two-step method has self-healing properties due to the introduction of multiple hydrogen bonds. The polymer chains of polyacrylic acid (PAA) and chitosan (CS) have relatively rich functional groups, including -COOH, -NH2, and -OH. x The MXene surface is rich in -OH, -F, and =O, which can form intermolecular hydrogen bonds and electrostatic interactions. The first hydrogen bond is the reaction between -COOH in PAA and -NH2 in CS to form a hydrogen bond; the second hydrogen bond is the reaction between CoS / Ti3C2T x Ti3C2T in inversion heterojunction x -OH / -F on the MXene surface reacts with -OH in CS to form hydrogen bonds; the third hydrogen bond is CoS / Ti3C2T x Ti3C2T in heterojunction xThe -OH / -F on the surface of MXene reacts with -COOH to form hydrogen bonds. The triple hydrogen bond force is strong and equivalent to a covalent bond, which makes the hydrogel self-healing. The performance of the healed material is more stable, and the repair interface of the hydrogel after self-healing is still clear without any diffusion.

[0017] 3. CoS / Ti3C2T prepared by hydrothermal method x MXene inverse heterojunction powder material, Ti3C2T x The general formula of MXene is M n+1 X n T x , n is 1, 2 or 3, M represents a transition metal, X represents C and / or N, T x CoS represents surface groups (OH, O or F) and is a new type of 2D transition metal carbonitride with metallic conductivity and hydrophilicity. It is an electrode material for high specific capacitance supercapacitors with hydrogels, which can provide excellent electrochemical energy storage at high charge / discharge rates. CoS, as a type of transition metal sulfide, is a promising candidate for Ti3C2T due to its relatively high theoretical capacity, low cost, weak Co-S bond, and multiple valence states. x MXene composite is a highly conductive material that improves electrochemical performance. x When the mass fraction of MXene is 0.1wt%, CoS / Ti3C2T x MXene has the best electrochemical performance, with a specific capacitance of 163 F / g; while CoS / Ti3C2T x The reduction in the MXene bandgap width proves that the inverse heterojunction has been successfully prepared. The heterostructured material can store energy through near-surface ion adsorption and additional contributions from fast reversible Faraday reactions. The generation of active sites and defects in the particles causes the boundaries of the heterostructured material to lead to multiple redox activities, excellent ionic conductivity and short diffusion paths; the interface effect heterostructure gives the electrode material good conductivity and mechanical strength, which will help improve the electrode material's ion storage capacity, rate performance and cycle stability. In addition, CoS nanoparticles can effectively inhibit the Ti3C2T x Aggregation and overlap of MXene nanosheets and improved stability; Ti3C2T x The MXene "accordion" structure provides an effective guarantee for the loading of CoS nanoparticles.

[0018] 4. The PCCT conductive hydrogel electrode prepared by the two-step method has a specific capacitance of 3.6F / g at a current density of 4mA / g; at a current density of 10mA / g, the cycle stability is still as high as 80% after 2000 cycles; after the PCCT conductive hydrogel is cured at room temperature for 48h, the self-healing efficiency can reach 66.88%. The conductive hydrogel prepared by the present invention provides a new idea for the derivation of multifunctional, intelligent and flexible electronic products. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 CoS / Ti3C2T prepared in Example 2 of the present invention x MXene inversion heterojunction (Ti3C2T x Scanning electron microscopy image of electrode material with a MXene mass fraction of 0.1 wt%; Figure 2 The CoS / Ti3C2T prepared in Example 2 is used in Example 6 of the present invention. x Scanning electron microscopy image of PPCT conductive hydrogel electrode material prepared by MXene inverse heterojunction; Figure 3 CoS / Ti3C2T prepared in Example 2 of the present invention x MXene inversion heterojunction (Ti3C2T x The absorbance of the electrode material with a mass fraction of MXene of 0.1 wt% and its relationship with wavelength, (α h n) 2 and h n relationship diagram; Figure 4 CoS / Ti3C2T prepared in Example 2 of the present invention x MXene inversion heterojunction (Ti3C2T x Constant current charge-discharge (GCD) curve of electrode material with a mass fraction of MXene of 0.1 wt% at a current density of 1 A / g; Figure 5 The CoS / Ti3C2T2 of Example 2 is used in Example 6, Comparative Example 3 and Comparative Example 4 of the present invention. x The constant current charge-discharge (GCD) curve of the conductive hydrogel electrode material prepared by MXene inverse heterojunction at a current density of 4 mA / g; Figure 6 The CoS / Ti3C2T prepared in Example 2 is used in Example 6 of the present invention. x Cyclic stability test curve of conductive hydrogel electrode material prepared by MXene inverse heterojunction at a current density of 10mA / g; Figure 7 The CoS / Ti3C2T prepared in Example 2 is used in Example 6 of the present invention.x Self-healing property test results of conductive hydrogel electrode materials prepared by MXene inverse heterojunction. DETAILED DESCRIPTION

[0020] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the following will be combined with the attached Figures 1 to 7 The technical solutions of the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0021] Example 1: The “accordion-shaped” Ti3C2T x Specific preparation steps of Mxene nanosheets: (1) Under ice bath conditions, weigh 2.25 g of Ti3AlC2 powder and slowly add it into 15 ml of 40% HF solution and stir for 30 min. Etch it in a 37°C water bath for 8 h. After etching, discard the supernatant and wash the black precipitate with deionized water by centrifugation at a centrifugal speed of 5000 rpm until the pH value of the supernatant is greater than or equal to 6.

[0022] (2) The obtained black precipitate was dissolved in 100 ml of deionized water, and the mixture was ultrasonically treated for 1 h at an ultrasonic power of 500 W in an ice bath with Ar gas continuously flowing therein, and then centrifuged at a centrifugal speed of 3500 rpm for 1 h.

[0023] (3) The black precipitate obtained by centrifugation was dried in a vacuum oven at 60°C for 12 h to obtain an accordion-shaped Ti3C2T x MXene nanosheets.

[0024] Example 2: CoS / Ti3C2T of the present invention x Specific preparation steps of MXene inverse heterojunction powder: (1) Add 7 mmol CoCl2·6H2O and 28 mmol thiourea to 60 ml ethylene glycol solution. The volume ratio of ethylene glycol solution is V 水 :V 乙二醇 =4:1, stir and mix thoroughly for 20 minutes.

[0025] (2) Add 0.1wt% of “accordion-shaped” Ti3C2T x Mxene nanosheets were treated at an ultrasonic power of 500 W for 20 min.

[0026] (3) The obtained mixed solution was transferred to a 100 mL high pressure reactor (PPL material), placed in an electric heated blast drying oven, and kept warm at 180° C. for 16 h.

[0027] (4) After the autoclave is cooled to room temperature, the mixed solution is washed with deionized water and anhydrous ethanol and centrifuged to precipitate. The precipitate is placed in a vacuum drying oven and dried at 50°C for 18 hours to obtain CoS / Ti3C2T x MXene inverse heterojunction powder.

[0028] The synthesized CoS / Ti3C2T x MXene inversion heterojunction electrode (Ti3C2T x The mass fraction of MXene is 0.1wt% and the specific capacitance is 163F / g at a current density of 1A / g.

[0029] Example 3: CoS / Ti3C2T of the present invention x Specific preparation steps of MXene inverse heterojunction powder: (1) Add 7 mmol CoCl2·6H2O and 28 mmol thiourea to 60 ml ethylene glycol solution. The volume ratio of ethylene glycol solution is V 水 :V 乙二醇 =4:1, stir and mix thoroughly for 20 minutes.

[0030] (2) Add 0.3wt% of “accordion-shaped” Ti3C2T x Mxene nanosheets were treated at an ultrasonic power of 500 W for 20 min.

[0031] (3) The obtained mixed solution was transferred to a 100 mL high pressure reactor (PPL material), placed in an electric heated blast drying oven, and kept warm at 180° C. for 16 h.

[0032] (4) After the autoclave is cooled to room temperature, the mixed solution is washed with deionized water and anhydrous ethanol and centrifuged to precipitate. The precipitate is placed in a vacuum drying oven and dried at 50°C for 18 hours to obtain CoS / Ti3C2T x MXene inverse heterojunction powder.

[0033] The synthesized CoS / Ti3C2T x MXene inversion heterojunction electrode (Ti3C2T x The mass fraction of MXene is 0.3wt% and the specific capacitance is 117F / g at a current density of 1A / g.

[0034] Example 4: CoS / Ti3C2T of the present invention x Specific preparation steps of MXene inverse heterojunction powder: (1) Add 7 mmol CoCl2·6H2O and 28 mmol thiourea to 60 ml ethylene glycol solution. The volume ratio of ethylene glycol solution is V 水 :V 乙二醇 =4:1, stir and mix thoroughly for 20 minutes.

[0035] (2) Add 0.4wt% of “accordion-shaped” Ti3C2T x Mxene nanosheets were treated at an ultrasonic power of 500 W for 20 min.

[0036] (3) The obtained mixed solution was transferred to a 100 mL high pressure reactor (PPL material), placed in an electric heated blast drying oven, and kept warm at 180° C. for 16 h.

[0037] (4) After the autoclave is cooled to room temperature, the mixed solution is washed with deionized water and anhydrous ethanol and centrifuged to precipitate. The precipitate is placed in a vacuum drying oven and dried at 50°C for 18 hours to obtain CoS / Ti3C2T x MXene inverse heterojunction powder.

[0038] The synthesized CoS / Ti3C2T x MXene inversion heterojunction electrode (Ti3C2T x The mass fraction of MXene is 0.4wt% and the specific capacitance is 111F / g at a current density of 1A / g.

[0039] Example 5: CoS / Ti3C2T of the present invention x Specific preparation steps of MXene inverse heterojunction powder: (1) Add 7 mmol CoCl2·6H2O and 28 mmol thiourea to 60 ml ethylene glycol solution. The volume ratio of ethylene glycol solution is V 水 :V 乙二醇 =4:1, stir and mix thoroughly for 20 minutes.

[0040] (2) Add 0.5wt% of “accordion-shaped” Ti3C2T x Mxene nanosheets were treated at an ultrasonic power of 500 W for 20 min.

[0041] (3) The obtained mixed solution was transferred to a 100 mL high pressure reactor (PPL material), placed in an electric heated blast drying oven, and kept warm at 180° C. for 16 h.

[0042] (4) After the autoclave is cooled to room temperature, the mixed solution is washed with deionized water and anhydrous ethanol and centrifuged to precipitate. The precipitate is placed in a vacuum drying oven and dried at 50°C for 18 hours to obtain CoS / Ti3C2T x MXene inverse heterojunction powder.

[0043] The synthesized CoS / Ti3C2T x MXene inversion heterojunction electrode (Ti3C2T x The mass fraction of MXene is 0.5wt% and the specific capacitance is 105F / g at a current density of 1A / g.

[0044] Example 6: CoS / Ti3C2T of the present invention x Preparation method of MXene inverse heterojunction self-healing conductive hydrogel electrode material, the preparation method comprising CoS / Ti3C2T x Two-step method for MXene inverse heterojunction powder and PCCT conductive hydrogel electrode material. The specific preparation steps are as follows: 0.24 g CS was dissolved in 6 ml of 2 wt% glacial acetic acid solution, and then 3 g acrylic acid (AA) was added and stirred evenly, which was marked as solution A. Then 0.05 g APS initiator and 0.081 g FeCl3•6H2O crosslinker were dissolved in 6 ml deionized water, which was marked as solution B. 0.31 wt% of CoS / Ti3C2T prepared in Examples 2 to 5 was added to solution B. x The MXene inverse heterojunction powder was ultrasonically treated for 30 minutes. Then, solution B was added to solution A, stirred evenly, and then inverted into a mold, which was placed in a forced air drying oven at 50°C for full reaction for 5 hours to obtain a PAA single physical network conductive hydrogel; then the PAA single physical network conductive hydrogel was immersed in a saturated sodium chloride solution for 1.5 hours to make the CS physical chains entangled, and a PCCT conductive hydrogel electrode material with a double physical cross-linked network structure was obtained. When the hydrogel is formed, due to the entanglement of the polymer chains, the CoS / Ti3C2T x MXene was successfully integrated into the hydrogel network, and the conductive hydrogel needed to be sealed before testing.

[0045] After testing, the synthesized PCCT conductive hydrogel electrode has a specific capacitance of 3.6F / g at a current density of 4mA / g; at a current density of 10mA / g, the cycle stability is still as high as 80% after 2000 cycles. After the PCCT conductive hydrogel heals at room temperature for 48h, the self-healing efficiency can reach 66.88%.

[0046] The present invention adopts a two-step method to quickly and efficiently synthesize PAA / CS / CoS / Ti3C2T with room temperature self-healing properties x MXene (PCCT) conductive hydrogel electrode material, CoS / Ti3C2T with high conductivity x MXene inverse heterojunction combined with PAA / CS hydrogel matrix, CoS effectively suppresses the active material Ti3C2T under high mass loading x The accumulation of MXene and the physical double network structure give the conductive hydrogel self-healing properties. CoS / Ti3C2T3 synthesized in situ by hydrothermal method x MXene inverse heterojunction powder materials, CoS and Ti3C2T x MXene can generate abundant interfaces and form abundant active centers, thus obtaining high charge transfer rate and having good electrochemical activity. x MXene helps to improve the wettability of the electrode, thereby shortening the length of the electrode / electrolyte migration path and accelerating ion diffusion. CoS nanoparticles can effectively inhibit the x The restacking of MXene improves its stability. Compared with hydrogels with only a single conductive filler, CoS / Ti3C2T x The presence of CoS as an electron bridge in the MXene inversion heterojunction accelerates the transfer of photogenerated electrons, thus making the CoS / Ti3C2T x MXene has better electrochemical properties. The conductive hydrogel electrode material prepared by the two-step method has self-healing properties due to the introduction of multiple hydrogen bonds. The polymer chains of PAA and CS have relatively rich functional groups, including -COOH, -NH2, and -OH. x The MXene surface is rich in -OH, -F, and =O, which can form intermolecular hydrogen bonds and electrostatic interactions. The first hydrogen bond is the reaction between -COOH in PAA and -NH2 in CS to form a hydrogen bond; the second hydrogen bond is the reaction between CoS / Ti3C2T x Ti3C2T in inversion heterojunction x -OH / -F on the MXene surface reacts with -OH in CS to form hydrogen bonds; the third hydrogen bond is CoS / Ti3C2T x Ti3C2T in heterojunction xThe -OH / -F on the surface of MXene reacts with -COOH to form hydrogen bonds. The triple hydrogen bond force is strong and equivalent to a covalent bond, which makes the hydrogel self-healing. The performance of the healed material is more stable, and the repair interface of the hydrogel after self-healing is still clear without any diffusion.

[0047] The present invention also discloses a CoS / Ti3C2T x MXene inverse heterojunction self-healing conductive hydrogel electrode material, CoS / Ti3C2T x The MXene inverse heterojunction conductive hydrogel electrode material is prepared by the preparation method of Example 6.

[0048] The present invention also discloses a CoS / Ti3C2T x Application of MXene inverse heterojunction self-healing conductive hydrogel electrode materials in the preparation of positive and negative electrodes of flexible all-solid-state supercapacitors.

[0049] Comparative Example 1: 7 mmol CoCl2·6H2O and 28 mmol thiourea were added to 60 ml ethylene glycol solution, the volume ratio of the ethylene glycol solution was V 水 :V 乙二醇 =4:1, stir and mix thoroughly for 20 minutes. The obtained mixed solution was transferred to a 100mL high-pressure reactor (PPL material), placed in an electric blast drying oven, and kept warm for 16 hours at 180°C. After the high-pressure reactor was cooled to room temperature, the mixed solution was washed with deionized water and anhydrous ethanol and centrifuged, and the precipitate was placed in a vacuum drying oven and dried at 50°C for 18 hours to obtain CoS powder.

[0050] The specific capacitance of the synthesized CoS electrode was detected to be 118 F / g at a current density of 1 A / g.

[0051] Comparative Example 2: 0.24 g CS was dissolved in 6 ml of 2 wt% glacial acetic acid solution, and then 3 g AA was added and stirred evenly, which was marked as solution A. Then 0.05 g APS initiator and 0.081 g FeCl3•6H2O crosslinker were dissolved in 6 ml deionized water, which was marked as solution B. 0.31 wt% of Ti3C2T prepared in Example 1 was added to solution B. x The MXene nanosheets were ultrasonically treated for 30 minutes. Then, solution B was added to solution A, stirred evenly, and then inverted into a mold, placed in a forced air drying oven at 50°C for full reaction for 5 hours, and a PAA single physical network conductive hydrogel was obtained; then the PAA single physical network conductive hydrogel was immersed in a saturated sodium chloride solution for 1.5 hours to make the CS physical chains entangled, and a PCT conductive hydrogel electrode material with a double physical cross-linked network structure was obtained.

[0052] After testing, the synthesized PCT conductive hydrogel electrode has a specific capacitance of 291.8 mF / g at a current density of 4 mA / g; the self-healing efficiency of the PCT conductive hydrogel can reach 50% after healing at room temperature for 48 hours. When the hydrogel is formed, due to the entanglement of the polymer chains, the Ti3C2T x MXene was successfully integrated into the hydrogel network, and the conductive hydrogel needed to be sealed before testing.

[0053] Comparative Example 3: Take 0.24g CS and dissolve it in 6 ml of 2wt% glacial acetic acid solution, then add 3g AA and stir evenly, marked as solution A. Then 0.05g APS initiator and 0.081g FeCl3•6H2O crosslinker are dissolved in 6 ml deionized water, marked as solution B, and 0.31wt% of CoS powder prepared in Comparative Example 1 is added to solution B for ultrasonic treatment for 30min. Then add solution B to solution A, stir evenly and invert the mold, place it in a blast drying oven at 50℃ and fully react for 5h, and a conductive hydrogel with a single physical network of PAA can be obtained; then the conductive hydrogel with a single physical network of PAA is immersed in a saturated sodium chloride solution for 1.5h, so that the CS physical chain is entangled, and a PCC conductive hydrogel electrode material with a double physical crosslinked network structure is obtained. When the hydrogel is formed, due to the entanglement of the polymer chain, CoS is successfully integrated into the hydrogel network, and the conductive hydrogel needs to be sealed and stored before testing.

[0054] After testing, the synthesized PCC conductive hydrogel electrode has a specific capacitance of 3.24 F / g at a current density of 4 mA / g; after the PCC conductive hydrogel heals at room temperature for 48 hours, the self-healing efficiency can reach 58.3%.

[0055] The materials used in Examples 1 to 6 of the present invention and Comparative Examples 1 to 3 are all conventional commercially available products and can be purchased.

[0056] CoS / Ti3C2T prepared in Examples 1 to 6 of the present invention and Comparative Examples 1 to 3 x The method for detecting the capacitance of the MXene inverse heterojunction self-healing conductive hydrogel electrode material is as follows: The electrochemical performance of the electrode was tested using a CHI660E electrochemical workstation. The three-electrode system was a working electrode, a Pt sheet as a counter electrode, and Hg / HgO as a reference electrode. The electrolyte was 1M KOH. The scan rate of cyclic voltammetry (CV) was 5~200 mV / s. The constant current charge / discharge (GCD) used different current densities to test the charge and discharge time of the electrode. The test frequency of electrochemical impedance spectroscopy (EIS) was 0.01~100kHz. The mass specific capacitance of the electrode material was calculated by the following formula: ; Where: I is the current / A, Δt is the discharge time / s, m ​​is the mass of active substance of the electrode material / g, and Δv is the voltage window.

[0057] CoS / Ti3C2T prepared in Examples 1 to 6 of the present invention and Comparative Examples 1 to 3 x The detection method of the room temperature self-healing properties of MXene inverse heterojunction self-healing conductive hydrogel electrode material is as follows: The conductive hydrogel was made into a cylindrical specimen with a diameter of 15.5 mm and a height of 100 mm, then cut into two halves, and then immediately contacted together and placed in a constant temperature and humidity incubator for 48 hours, with fixed temperature and humidity (25°C, 80% RH) to minimize water evaporation. At room temperature, a universal testing machine was used with a tensile rate of 50 mm / min. Each sample was repeated at least three times, and the average value was taken as the final result (the conductive hydrogel after self-healing was marked as H-PC, H-PCT, H-PCC, H-PCCT, H-PCS, H-PCST, H-PCU, H-PCUT, H-PCP, H-PCPT). The self-healing and efficiency (HE) of the conductive hydrogel can be calculated by the following formula: ; Where: ε h is the elongation at break of the conductive hydrogel after self-healing, and ε0 is the initial elongation at break of the conductive hydrogel.

[0058] Figure 1 Ti3C2T x CoS / Ti3C2T prepared when the mass fraction of MXene is 0.1 wt% x Scanning electron microscope image of MXene inverse heterojunction electrode material, Figure 1 It can be seen that Ti3C2T x In addition to the uniform loading of a large number of CoS nanoparticles on the surface of the MXene layer, a large number of CoS are also uniformly loaded between the layers and at the edges of the layers, indicating that Ti3C2Tx The “accordion-like” layered structure of MXene is beneficial for the loading of CoS nanoparticles. In addition, the CoS nanoparticles attached to the interlayers can expand the Ti3C2T x The interlayer spacing of MXene prevents Ti3C2T x The restacking of MXene sheets promotes the transfer of ions between electrode materials / electrolyte, which can further improve the electrochemical performance of electrode materials.

[0059] Figure 2 For CoS / Ti3C2T x Scanning electron microscopy image of PPCT conductive hydrogel electrode material prepared by MXene inverse heterojunction. Figure 2 It can be seen that the PPCT conductive hydrogel electrode has an obvious irregular pore structure. This is because in the formation process of the conductive hydrogel, the first step is to use APS as an initiator and Fe 3+ As a crosslinking agent, AA polymer monomers were polymerized in situ at 50 °C, that is, Fe 3+ The first physical cross-linking network is generated by the ionic coordination of -COOH on the AA chain; the second step is to immerse it in a saturated sodium chloride solution, and the aggregation and chain entanglement of the CS molecular chains in the saturated sodium chloride solution form a second physical cross-linking network. The salting-out effect reduces the electrostatic repulsion between CS molecules and enhances the hydrophobic force, causing the molecular chains to move and aggregate. The second physical entanglement network formed by aggregation can significantly improve the mechanical properties, toughness and stiffness of the hydrogel. During the formation of the hydrogel, CoS / Ti3C2T x MXenes are successfully incorporated into hydrogel networks due to polymer chain entanglement.

[0060] Figure 3 Ti3C2T x CoS / Ti3C2T prepared when the mass fraction of MXene is 0.1 wt% x Absorbance and wavelength of MXene inverse heterojunction electrode materials, (α h n) 2 and h n relationship diagram; by Figure 3 (a) It can be seen that the UV-vis spectrum verifies the Ti3C2T x The introduction of MXene makes CoS / Ti3C2T x The inversion heterojunction exhibits better performance than pristine CoS and Ti3C2T in the wavelength range of 200~700 nm. x MXene has stronger absorbance; Figure 3 (b) It can be seen that CoS / Ti3C2T x The band gap of MXene inversion heterojunction is 0.78 eV, which is smaller than that of Ti3C2T xMXene (1.1 eV) and pure CoS (1.62 eV) are much lower, indicating that Ti3C2T x The introduction of MXene significantly enhances the electrical conductivity of CoS / Ti3C2T x The MXene inversion heterojunction accelerates the rapid charge transfer and is beneficial to improving the electrochemical performance.

[0061] Figure 4 Ti3C2T x CoS / Ti3C2T prepared when the mass fraction of MXene is 0.1 wt% x The constant current charge-discharge (GCD) curve of MXene inverse heterojunction electrode material at a current density of 1A / g; Figure 4 It can be seen that at a current density of 1A / g, different Ti3C2T x MXene content in CoS / Ti3C2T x The GCD curves of MXene inverse heterojunctions have good stability and reversibility. x When the mass fraction of MXene is 0.1 wt%, CoS / Ti3C2T x The MXene inversion heterojunction has the longest charge and discharge time, with a specific capacitance of 163 F / g.

[0062] Figure 5 For Example 6, Comparative Example 2, and Comparative Example 3, CoS / Ti3C2T x The constant current charge-discharge (GCD) curve of the conductive hydrogel electrode material prepared by MXene inverse heterojunction at a current density of 4 mA / g; Figure 5 It can be seen that when the current density is 4 mA / g, the GCD curve of the PCCT conductive hydrogel electrode shows a longer charge and discharge time than other conductive hydrogel electrodes, and the specific capacitance is the largest (3.6 F / g).

[0063] Figure 6 For Example 6, CoS / Ti3C2T x Cyclic stability test curve of conductive hydrogel electrode material prepared by MXene inverse heterojunction at a current density of 10mA / g; Figure 6 It can be seen that the cycle life test of the PCCT conductive hydrogel electrode was cycled 2000 times at a current density of 10 mA / g, and the capacitance retention rate was 80%.

[0064] Figure 7 In Example 6 of the present invention, CoS / Ti3C2T x The self-healing properties test results of the conductive hydrogel electrode material prepared by MXene inverse heterojunction; Figure 7It can be seen that the self-healing efficiency of PCCT is 66.88%. When the PCCT conductive hydrogel is cut into two halves, the LED light will go out due to the open circuit; after the hydrogel self-heals, the LED lights up again and shows the same brightness; due to the presence of multiple hydrogen bonds, metal ion coordination and electrostatic attraction in the PCCT conductive hydrogel, these forces are dynamically reversible non-covalent bonds, which are partially destroyed when the hydrogel is damaged, so that the polymer segments have high mobility, and the mutual penetration entanglement and re-formation at the wound enable the hydrogel to repair the damage. The optical microscope photos of the healing incision of the PCCT conductive hydrogel over the healing time show that the PCCT conductive hydrogel was cut into two halves at room temperature, and then the cut parts were quickly connected together within 5s, gently squeezed and encapsulated; placed in a constant temperature and humidity chamber, taken out every 12 hours, and the healing process of the incision was observed with an optical microscope. As the healing time increases, the incision gap gradually becomes smaller and finally heals completely.

[0065] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A CoS / Ti3C2T x The preparation method of MXene inverse heterojunction self-healing conductive hydrogel electrode material is characterized in that: The preparation method comprises the following steps: Step 1: Prepare CoS / Ti3C2T x MXene inverse heterojunction powder; Step 2: Dissolve a certain amount of chitosan in glacial acetic acid solution and mix the CoS / Ti3C2T x MXene inverse heterojunction powder and aqueous solutions of acrylic acid, initiator and crosslinker were added to the above mixed solution and placed in a blast drying oven for full reaction; the reactants were immersed in a saturated sodium chloride solution to obtain a PAA / CS / CoS / Ti3C2T dual physical crosslinked network structure. x MXene conductive hydrogel electrode materials.

2. CoS / Ti3C2T according to claim 1 x The preparation method of MXene inverse heterojunction self-healing conductive hydrogel electrode material is characterized in that: Step 1 CoS / Ti3C2T x Specific preparation steps of MXene inverse heterojunction powder: Step S1: Add 7 mmol CoCl2·6H2O and 28 mmol thiourea into 60 ml ethylene glycol solution, the volume ratio of the ethylene glycol solution is V 水 :V 乙二醇 =4:1, stir and mix thoroughly for 20 minutes; Step S2: Add 0.1-0.5wt% of "accordion-shaped" Ti3C2T x Mxene nanosheets were treated at an ultrasonic power of 500 W for 20 min; Step S3: The mixed solution obtained in step S2 was transferred to a high-pressure reactor with a volume of 100 mL, placed in an electric heating blast drying oven, and kept warm at a temperature of 180° C. for 16 h; Step S4: After the autoclave is cooled to room temperature, the mixed solution is washed with deionized water and anhydrous ethanol and centrifuged to precipitate. The precipitate is placed in a vacuum drying oven and dried at 50°C for 18 hours to obtain CoS / Ti3C2T x MXene inverse heterojunction powder.

3. CoS / Ti3C2T according to claim 2 x The preparation method of MXene inverse heterojunction self-healing conductive hydrogel electrode material is characterized in that: The "accordion-shaped" Ti3C2T in step S2 x Specific preparation steps of Mxene nanosheets: Step S 21 : Under ice bath conditions, weigh 2.25g Ti3AlC2 powder and slowly add it into 15ml 40% HF solution, stir and mix, and etch it in a 37℃ water bath for 8h. After etching, wash it with deionized water by centrifugation at a centrifugal speed of 5000 rpm until the pH value of the supernatant is greater than or equal to 6; Step S 22 :Step S 21 The obtained black precipitate was dissolved in 100 ml of deionized water, and ultrasonically treated for 1 h at an ultrasonic power of 500 W in an ice bath with Ar gas continuously flowing, and then centrifuged at a centrifugal speed of 3500 rpm for 1 h. Step S 23 :Step S 22 The black precipitate obtained by centrifugation was dried in a vacuum oven at 60 °C for 12 h to obtain an "accordion" Ti3C2T x MXene nanosheets.

4. The CoS / Ti3C2T according to any one of claims 1 to 3 x The preparation method of MXene inverse heterojunction self-healing conductive hydrogel electrode material is characterized in that: In step 2, the amount of chitosan used is 0.24 g, the volume of the glacial acetic acid solution is 6 ml, and the solubility is 2 wt%.

5. CoS / Ti3C2T according to claim 4 x The preparation method of MXene inverse heterojunction self-healing conductive hydrogel electrode material is characterized in that: In step 2, the initiator is 0.05 g of ammonium persulfate, and the cross-linking agent is 0.081 g of FeCl3•6H2O. Ammonium persulfate and FeCl3•6H2O are dissolved in 6 ml of deionized water to prepare an aqueous solution.

6. CoS / Ti3C2T according to claim 5 x The preparation method of MXene inverse heterojunction self-healing conductive hydrogel electrode material is characterized in that: Step 2 CoS / Ti3C2T x The addition amount of MXene inverse heterojunction powder is 0.31wt%.

7. CoS / Ti3C2T according to claim 6 x The preparation method of MXene inverse heterojunction self-healing conductive hydrogel electrode material is characterized in that: The reaction temperature of the blast drying oven in step 2 is 50° C. and the reaction time is 5 h.

8. CoS / Ti3C2T according to claim 7 x The preparation method of MXene inverse heterojunction self-healing conductive hydrogel electrode material is characterized in that: In step 2, the soaking time in the saturated sodium chloride solution is 1.5 hours.

9. A CoS / Ti3C2T x MXene inverse heterojunction self-healing conductive hydrogel electrode material, characterized in that: CoS / Ti3C2T x The MXene inverse heterojunction conductive hydrogel electrode material is prepared by the preparation method described in claim 8.

10. A CoS / Ti3C2T as claimed in claim 9 x Application of MXene inverse heterojunction self-healing conductive hydrogel electrode materials in the preparation of positive and negative electrodes of flexible all-solid-state supercapacitors.